An Overview Of Cases Of Violence Against Women And Children In Tasikmalaya City - Neni Sholihat; Miftahul Falah; Rossy Rosnawanti; Heri Budiawan (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Since 1984, the Government of Indonesia has shown its concern for issues of women's empowerment and child protection. There are no fewer than a dozen policies issued by the government to manage and prevent incidents of violence against women and children. The city of Tasikmalaya is one of the cities that already has a mayoral regulation to manage this issue, by issuing mayoral regulation no. 102 of 2016 concerning woman empowerment and child protection. But, from year to year, the number of cases of violence against women and children is increasing, both quantitatively and qualitatively, with increasingly diverse types of violence. The purpose of this study was to see an overview of cases of violence against women and children in Tasikmalaya city. The Descriptive method with cross sectional approach was used in this study. The results showed that the most common type of violence was sexual harassment, with the most victims of violence being women, with the highest level of education of victim being elementary and junior high school, and the relationship between the perpetrator and the victim was mostly family, with the scene of the incident in the neighbourhood or a place known to the victim. In conclusion, female gender, elementary and junior high school education, and family are a real picture related to cases of violence against women and children in Tasikmalaya. It is recommended that socialization regarding the prevention of violence against women and children be carried out continuously. Improve the competence of officers who provide women and child protection services and periodic monitoring of service activities by including physical evidence of reporting as well.